Evaluasi Implementasi Putusan Mahkamah Konstitusi Terhadap Desain Surat Suara Calon Tunggal Dalam Pilkada - Oktavia, Enika Maya; Syafei, Rizki Maulana; Fatna, Tsalis Khoirul (UI Scholars Hub, 2025)
The phenomenon of single candidates in regional elections in Indonesia has created a dilemma in applying democratic principles, especially regarding ballot design that often confuses voters. The Constitutional Court’s Decision Number 100/PUU-XIII/2015 mandated a plebiscite design with “agree” or “disagree” options for single candidates. However, in practice, this design has been distorted with the presence of a blank box without adequate explanation. This study aims to evaluate the extent to which the discrepancy between the Constitutional Court's decision and actual ballot design practices affects voter understanding and the quality of democracy. This study employs a normative juridical method with a qualitative-descriptive approach, relying on literature reviews and secondary data analysis from legal documents and news reports. The theoretical framework uses the